Neuro-Nutraceutical Polyphenols: How Far Are We? - Gentile, Maria Teresa; Camerino, Iolanda; Ciarmiello, Loredana; Woodrow, Pasqualina; Muscariello, Lidia; De Chiara, Ida; Pacifico, Severina (Antioxidants, 2023)
The brain, composed of billions of neurons, is a complex network of interacting dynamical systems controlling all body functions. Neurons are the building blocks of the nervous system and their impairment of their functions could result in neurodegenerative disorders. Accumulating evidence shows an increase of brain-affecting disorders, still today characterized by poor therapeutic options. There is a strong urgency to find new alternative strategies to prevent progressive neuronal loss. Polyphenols, a wide family of plant compounds with an equally wide range of biological activities, are suitable candidates to counteract chronic degenerative disease in the central nervous system. Herein, we will review their role in human healthcare and highlight their: antioxidant activities in reactive oxygen species-producing neurodegenerative pathologies; putative role as anti-acetylcholinesterase inhibitors; and protective activity in Alzheimer’s disease by preventing Aβ aggregation and tau hyperphosphorylation. Moreover, the pathology of these multifactorial diseases is also characterized by metal dyshomeostasis, specifically copper (Cu), zinc (Zn), and iron (Fe), most important for cellular function. In this scenario, polyphenols’ action as natural chelators is also discussed. Furthermore, the critical importance of the role exerted by polyphenols on microbiota is assumed, since there is a growing body of evidence for the role of the intestinal microbiota in the gut–brain axis, giving new opportunities to study molecular mechanisms and to find novel strategies in neurological diseases.